The Foreign Language Teaching Anxiety Scale: Preliminary Tests of Validity and Reliability - Selami Aydin; Ozgehan Ustuk (National Research University Higher School of Economics, 2020)
Although anxiety in the foreign language learning context has been studied extensively, the anxiety experienced by foreign language teachers, who are important stakeholders of classroom contexts and language learners themselves, seems to be overlooked. While research mainly focuses on foreign language anxiety in a learning context, there is not sufficient research to contextualize foreign language teaching anxiety (FLTA). In addition, in the current literature, few studies were performed to measure FLTA. In light of this, this study aims to present the preliminary results of the validity and reliability of the Foreign Language Teaching Anxiety Scale (FLTAS). A background questionnaire and the FLTAS were administered to 100 senior pre-service teachers of English as a foreign language (EFL), before performing Cronbach's Alpha and exploratory factor analysis. The findings showed that the scale obtains a high reliability coefficient and internal consistency in a five-factor solution. The study ends with recommendations for further research.